2023
DOI: 10.32604/cmc.2023.032005
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Multiple Guava Leaf Disease Detection from a Single Leaf Using Hybrid Deep Learning Technique

Abstract: The guava plant has achieved viable significance in subtropics and tropics owing to its flexibility to climatic environments, soil conditions and higher human consumption. It is cultivated in vast areas of Asian and Non-Asian countries, including Pakistan. The guava plant is vulnerable to diseases, specifically the leaves and fruit, which result in massive crop and profitability losses. The existing plant leaf disease detection techniques can detect only one disease from a leaf. However, a single leaf may cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…The results showed that the proposed Deep Feature Fusion technique model performed better than the cited study. It prevented a fair comparison of the study's findings to those of other, more reliable studies 67‐69 …”
Section: Resultsmentioning
confidence: 95%
“…The results showed that the proposed Deep Feature Fusion technique model performed better than the cited study. It prevented a fair comparison of the study's findings to those of other, more reliable studies 67‐69 …”
Section: Resultsmentioning
confidence: 95%
“…It achieved 93.8% accuracy on the ISIC‐2017 dataset. Second, in 2021, Khan et al 20 . developed Deep CNN, which applied moth flame optimization with deep learning features to segment and classify skin lesions.…”
Section: Resultsmentioning
confidence: 99%
“…Dermoscopy is used to collect photographs of the skin, while a biopsy and a microscope are required to obtain images of other medical structures. 14 15,16 and other deep learning algorithms [17][18][19][20][21][22] have shown great progress in various skin cancer classifications, with excellent accuracy and robustness. Extraction of discriminative features from photos of skin lesions has been used to obtain outstanding classification results using DenseNet, 23 InceptionNet, 24 and ResNet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of deep learning (DL) can play a vital role in solving real-life problems after the advancements in computer systems, especially graphical processing units (GPUs). DL automation in areas of various domains is straightforward, such as medical [11,12], agriculture [13][14][15], proper water resources supply [16], facial expression identification [17] and in cities surveillance [18]. In recent years, the most exciting topic has been damage, cracks, and pothole detection of road surfaces using artificial intelligence.…”
Section: Introductionmentioning
confidence: 99%